The interaction of silver nanoparticles with triosephosphate isomerase from human and malarial parasite (Plasmodium falciparum) : a comparative study - De Moor, Warren Ralph Josephus (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
The advent of advanced modern nanotechnology techniques offers new and exciting opportunities to develop novel nanotech-derived antimalarial nanodrugs with enhanced selective and targeting abilities that allow for lower effective drug dosages, longer drug persistence and reduced drug degradation within the body. Using a nanodrug approach also has the advantage of avoiding drug resistance problems that plague reconfigured versions of already-existing antimalarial drugs. In this study recombinant triosephosphate isomerase enzymes from Plasmodium falciparum (PfTIM) and Humans (hTIM) were recombinantly expressed, purified and characterised. PfTIM was shown to have optimal pH stability at pH 5.0-5.5 and thermal stability at 25Â°C with Km 4.34 mM and Vmax 0.876 Î¼mol.mlâ »â‚‘minâ »â‚‘. For hTIM, these parameters were as follows: pH optima of 6.5-7.0; temperature optima of 30Â°C, with Km 2.27 mM and Vmax 0.714 Î¼mol.mlâ »â‚‘minâ »â‚‘. Recombinant TIM enzymes were subjected to inhibition studies using polyvinylpyrrolidone (PVP) stabilised silver nanoparticles (AgNPs) of 4-12 nm in diameter. These studies showed that the AgNPs were able to selectively inhibit PfTIM over hTIM with an 8-fold greater decrease in enzymatic efficiency (Kcat/Km) observed for PfTIM, as compared to hTIM, for kinetics tests done using 0.06 Î¼M of AgNPs. Complete inhibition of PfTIM under optimal conditions was achieved using 0.25 Î¼M AgNPs after 45 minutes while hTIM maintained approximately 31% of its activity at this AgNP concentration. The above results indicate that selective enzymatic targeting of the important, key metabolic enzyme TIM, can be achieved using nanotechnology-derived nanodrugs. It was demonstrated that the key structural differences, between the two enzyme variants, were significant enough to create unique characteristics for each TIM variant, thereby allowing for selective enzyme targeting using AgNPs. If these AgNPs could be coupled with a nanotechnology-derived, targeted localization mechanism "“ possibly using apoferritin to deliver the AgNPs to infected erythrocytes (Burns and Pollock, 2008) "“ then such an approach could offer new opportunities for the development of viable antimalarial nanodrugs. For this to be achieved further research into several key areas will be required, including nanoparticle toxicity, drug localization and testing the lethality of the system on live parasite cultures.
Keywords: Silver; Nanoparticles; Triose-phosphate isomerase; Plasmodium falciparum; Nanotechnology; Antimalarials; Povidone